CHARACTERISTICS OF 109 INDEX CASES IN TB OUTBREAK - INOUE, Takeo (Kekkaku, 2008)
[Objectives] To elucidate characteristics of index cases in TB outbreak. [Subjects and Methods] The subjects of this retrospective study were 109 index cases in TB outbreak observed in Japan between 2003 and 2005, and reported to the Ministry of Health. Labour and Welfare. An index case ra te (ICR) for a category of patients was defined as following; ICR=NI/NA, where NA: Number of TB patients in a category A, and NI: Number of index cases in category A. [Results] Of the 109 patients, 20 were female and 89 were male. Smear-positive pulmonary TB patients were 102 in number, and separated to 87 patients with cavitary lesion on a chest X-ray and 15 without cavitary lesion, and the remaining 7 patients were smear-negative and culture-positive pulmonary TB patients. The index case rates were 0.46% for smear-positive cavitary patients, 0.10% for smear-positive non-cavitary patients, and 0.04% for smear-negative culturepositive patients. The differences were highly significant between smear-positive cavitary patients and smear-positive non-cavitary patients, as well as between smear-positive cavitary patients and smear-negative culture-positive patients (p< 0.001). In 57 male patients with smear-positive cavitary lesion, the index case rates were significantly different between the thirties and the forties (1.84% vs 0.61%, p<0.01). All patients were grouped by age to a younger group with 10 to 39 years of age, a middle aged group with 40 to 69years, and an elder group with 70 years or higher. The index case rates in smear-positive cavitary patients were 2.32% for the male younger group, 0.37% for the male middle group, 0.06% for male elder group, 0.41 % for the female yo unger group, 0.37% for the female middle group, and 0% for female elder group. The differences were highly significant between the male younger group and the male middle group, as well as between the male younger group and the female younger group (p<0, 001). The index case rates for smearpositive cavitary patients were significantly higher than noncavitary patients in two categories; 1.58% versus 0.21 % for the younger group (p< 0.001), and 0.37% versus 0.11% for the middle aged group (p< 0.05). [Conclusion] These findi ngs suggest that TB outbreak risk is the highest in those patients categorized to be smear-positive, cavitary, younger group, and male.